2004
DOI: 10.1002/ca.10189
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of motor function of the deep fibular (peroneal) nerve by direct nerve transfer of branches from the tibial nerve: An anatomical study

Abstract: Traction injuries of the common fibular (peroneal) nerve frequently result in significant morbidity due to tibialis anterior muscle paralysis and the associated loss of ankle dorsiflexion. Because current treatment options are often unsuccessful or unsatisfactory, other treatment approaches need to be explored. In this investigation, the anatomical feasibility of an alternative option, consisting of nerve transfer of motor branches from the tibial nerve to the deep fibular nerve, was studied. In ten cadaveric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 18 publications
1
64
0
Order By: Relevance
“…Our measurements of nerve diameter and crosssectional areas are consistent with those reported by Bodily et al [27]. However, dimensions of cross-sections in the nerve (sex unknown) examined by McKinley were consistently smaller than those found in our study [17].…”
Section: Anatomy and Morphologysupporting
confidence: 92%
“…Our measurements of nerve diameter and crosssectional areas are consistent with those reported by Bodily et al [27]. However, dimensions of cross-sections in the nerve (sex unknown) examined by McKinley were consistently smaller than those found in our study [17].…”
Section: Anatomy and Morphologysupporting
confidence: 92%
“…The peroneal nerve, often ruptured in knee dislocations, can sustain an injury from its proximal origin high in the popliteal fossa to several centimeters distal to the fibular head, a distance spanning greater than 15 cm [1,16]. The common peroneal nerve injury results in loss of sensation to the dorsum of the foot and gait-altering paralysis of the tibialis anterior and the peroneus muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Users of AFOs are generally unsatisfied and noncompliant with the device because of discomfort, hygiene, and mobility issues [1,21]. One study suggests operative exploration is indicated in a recognized nerve laceration or any open or closed injury that fails to show recovery by clinical or electromyographic examination 3 months or more after injury [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the 272 patients who had stretch/contusion from high-velocity injuries were involved in motor vehicle accidents. Of 272 stretch/contusion cases, 84 (approximately 30%) were identified as sports-related (Table 1), which included skiing (42 cases), football (23), soccer (8), basketball (6), ice hockey (2), track (2), and volleyball (1). The 84 sports-related peroneal nerve injuries were categorized into those without fracture/dislocation (48 cases) and those with fracture/ dislocation (36 cases).…”
Section: Patient Populationmentioning
confidence: 99%